In the Quest of Low‐Frequency Impedance Spectra of Efficient Perovskite Solar Cells. Issue 7 (28th May 2021) - Prochowicz, Daniel; Trivedi, Suverna; Parikh, Nishi; Saliba, Michael; Kalam, Abul; Mahdi Tavakoli, Mohammad; Yadav, Pankaj
Abstract : Measurement and understanding of electrochemical impedance spectroscopy of perovskite solar cells (PSCs) are nontrivial, as perovskite absorbers are a mixed conductor exhibiting both ionic and electronic motion. Moreover, the interpretation of the low‐frequency spectra especially low‐frequency resistance ( R LF ) is ambiguous. Some reports suggest that R LF is related to ionic transport resistance, whereas others attribute it with the recombination processes. Herein, more light is put on the quest of low‐frequency impedance spectra of efficient PSCs. It is found that high‐ and low‐frequency resistances ( R HF and R LF ) follow a similar dependence on the applied bias and illumination with a comparable slope. These resistances are associated with the recombination processes in PSCs. The relation between low‐frequency spectra of PSCs and the physical parameters such as the role of the interface, grains' sizes, and perovskite composition is studied. It is found that the low‐frequency spectra of PSCs mainly depend on the grains' sizes and shift toward the high frequency, i.e., toward faster time constants with increasing the grain size. It is observed that these devices exhibit the lower recombination and higher open‐circuit voltage. A convenient way for the in‐depth analysis of PSCs, which will be crucial for designing better‐performing PSCs, is provided. Abstract : The relation between low‐frequency electrochemical impedance spectroscopy of the perovskite solar cell and its physical parameters such as the role of interface, grains' sizes, and perovskite composition is systematically established.